Influence Of Perceptions Of Safety And Programs Occupational Health (POH) On Work Achievement Wear Personal Protective Equipment (PPE) Maritime Task - Fiernanda Yutimura; Moch Haris (The Kalimantan Social Studies Journal, 2023)
This study aims to analyze and prove the effect of perceptions of occupational safety and health on the work performance of KRI soldiers and to mediate the motivation to use personal protective equipment (PPE) between K3 perceptions and work performance. The study population was soldiers of the Indonesian National Armed Forces (TNI) Navy who served on the Republic of Indonesia Ship (KRI) KRI, while the number of samples studied reached 370 people. The analysis technique uses Struqtural Equation Modeling (SEM) structural equation modeling. The results showed that there was a significant influence between perceptions of occupational safety and occupational health on soldier performance. The path coefficient between X1 to Y is 0.197 with a p-value of 0.032 while the variable X2 to Y has a path coefficient of 0.351 with a p-value of 0.000. Mediating motivation to use PPE is also significant between variables X1 and X2 on work performance. The coefficient X1 on Z, for example, obtained a value of 0.316 and the coefficient X2 on Z was 0.49, while the effect of Z itself on Y was 0.255. All of these variables have a p-value below 5%. The magnitude of the indirect effect of X2 on Y is 0.125 and X1 on Y is 0.081. This means that Z is more dominant in mediating X2 to Y than X1 to Y.